Pesantren 5.0: Transforming Islamic Educational Thought in Facing Artificial Intelligence and the Global Knowledge Society - Budiyanto Budiyanto; Ahmad Tanzeh; Agus Purwowidodo (Education and Sociedad Journal, 2025)
The rapid development of Artificial Intelligence (AI) and the emergence of a global knowledge society have created new challenges and opportunities for Islamic educational institutions, particularly pesantren. This study aims to analyze the transformation of Islamic educational thought within the framework of “Pesantren 5.0” as a strategic response to technological disruption, digital civilization, and the increasing demands of global competitiveness. This research employs a qualitative literature review approach by examining scholarly articles, books, policy documents, and contemporary studies related to Islamic education, digital transformation, and AI integration. The findings reveal that Pesantren 5.0 represents a paradigm shift from traditional knowledge transmission toward an adaptive, innovative, and technology-oriented educational model while maintaining Islamic values and pesantren traditions. The transformation encompasses curriculum redesign, digital literacy enhancement, AI-assisted learning systems, strengthening critical and ethical thinking, and the development of global competencies grounded in Islamic worldview. Furthermore, pesantren are positioned not only as centers of religious learning but also as institutions capable of producing human resources who are intellectually competent, technologically literate, and morally responsible. The study concludes that the successful implementation of Pesantren 5.0 requires the integration of technological innovation, educational leadership, and value-based learning. The implications of this research emphasize the importance of developing a sustainable Islamic educational ecosystem that harmonizes tradition, innovation, and digital transformation to prepare Muslim generations for the challenges of the AI era and the global knowledge society.